2003
DOI: 10.1124/mol.64.2.382
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modes of Action of Artesunate in Tumor Cell Lines

Abstract: A profound cytotoxic action of the antimalarial, artesunate (ART), was identified against 55 cancer cell lines of the U.S. National Cancer Institute (NCI). The 50% inhibition concentrations (IC 50 values) for ART correlated significantly to the cell doubling times (P ϭ 0.00132) and the portion of cells in the G 0 /G 1 (P ϭ 0.02244) or S cell cycle phases (P ϭ 0.03567). We selected mRNA expression data of 465 genes obtained by microarray hybridization from the NCI data base. These genes belong to different biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
298
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 398 publications
(319 citation statements)
references
References 33 publications
15
298
1
5
Order By: Relevance
“…It is unknown yet, whether ARS derivatives belong to this category, as its prolonged use has not been reported. However, given its efficacy against drug-resistant tumor cells 17,19 and the relation to antiangiogenesis, it appears to be well-suited for adjuvant therapy in combination with classical chemotherapy. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unknown yet, whether ARS derivatives belong to this category, as its prolonged use has not been reported. However, given its efficacy against drug-resistant tumor cells 17,19 and the relation to antiangiogenesis, it appears to be well-suited for adjuvant therapy in combination with classical chemotherapy. …”
Section: Discussionmentioning
confidence: 99%
“…14 The observation that ART inhibits the growth of many transformed cell lines has led to the hypothesis that the drug can also be useful for the treatment of human neoplasia. [15][16][17][18][19][20][21][22][23][24] As shown by us and others, [25][26][27][28][29][30][31][32] ARSs reveal antiangiogenic features in vitro and in vivo. The molecular determinants of the antiangiogenic activity of ARSs are incompletely understood at present.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest a potential use of artemisinin and its active metabolite DHA as anticancer agents (6,(30)(31)(32). However, the molecular details of DHA-induced apoptosis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Large clinical studies with malaria patients have shown that ART is well tolerated, with a few and insignificant side effects [8][9][10]. In addition to the well known anti-malarial activity of ART, recently a cytotoxic action of ART against cancer cell lines of different tumor types is identified [11][12][13][14][15][16]. Until now, the accepted antitumor mechanism is similar to the antimalarial mechanism; the artemisinin structure contains an endoperoxide bridge that reacts with an iron atom to form free radicals [17][18][19], which causes macromolecular damage and cell death [20].…”
Section: Introductionmentioning
confidence: 99%